The Expression of Irony, Taunt and Parable in Tahir Malik's Works (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses a number of issues in Uzbek linguistics, such as checking the semantic structure of language units, delimiting their stylistic-semantic meanings, and determining the place of language tools in the realization of these meanings in speech. In particular, Tahir Malik's use of phonetic, lexical, morphological and syntactic units in the language as a means of creating a unique style, the peculiarities of creating a unique style, and the study of the artistic text in the stylistic aspect are expressed.